2014
DOI: 10.1016/j.jamcollsurg.2014.04.022
|View full text |Cite
|
Sign up to set email alerts
|

Remnant Growth Rate after Portal Vein Embolization Is a Good Early Predictor of Post-Hepatectomy Liver Failure

Abstract: Background After portal vein embolization (PVE), the future liver remnant (FLR) hypertrophies over several weeks. An early marker that predicts a low risk of post-hepatectomy liver failure may reduce the delay to surgery. Study Design Liver volumes of 153 patients who underwent a major hepatectomy (>3 segments) after PVE for primary or secondary liver malignancy between September 1999 and November 2012 were retrospectively evaluated with computerized volumetry. Pre- and post-PVE FLR volume and functional liv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
38
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 87 publications
(46 citation statements)
references
References 48 publications
5
38
0
3
Order By: Relevance
“…This is the first study to describe serial changes in plasma biomarker levels after partial hepatectomy in a uniform population. It is well known that liver regeneration is rapid in the first 2 weeks after liver resection, but it continues for many weeks after partial hepatectomy; plus, the factors involved in termination of liver regeneration are not well known. Another key point of this study is that the biomarkers were analyzed until the end of 6 weeks after hepatectomy in order to study the markers involved in the termination of liver regeneration process.…”
Section: Discussionmentioning
confidence: 99%
“…This is the first study to describe serial changes in plasma biomarker levels after partial hepatectomy in a uniform population. It is well known that liver regeneration is rapid in the first 2 weeks after liver resection, but it continues for many weeks after partial hepatectomy; plus, the factors involved in termination of liver regeneration are not well known. Another key point of this study is that the biomarkers were analyzed until the end of 6 weeks after hepatectomy in order to study the markers involved in the termination of liver regeneration process.…”
Section: Discussionmentioning
confidence: 99%
“…6,28 Recent data support this hypothesis with the use of non-parametric regression and showed that post embolization, no patient with a growth rate .2.66% per week developed liver failure. 29 In patients with chronic liver disease, some investigators have adopted algorithms incorporating functional tests, such as the indocyanine green retention rate, which has been proposed as an adjunct to the volumetric measurements. 30,31 However, despite encouraging results, widespread clinical acceptance is lacking so far.…”
Section: Discussionmentioning
confidence: 99%
“…The conventional strategy to avoid postoperative liver failure involves determination of the future remnant liver volume and, when indicated, selective portal vein embolization together with degree of hypertrophy of remnant liver 5 . In cases of anticipated insuficient hypertrophy such as patients with severe steatosis, long-term chemotherapy and cirrhosis CH can be considered.…”
Section: Discussionmentioning
confidence: 99%